Predição do peso e do rendimento de filé de tilápia do nilo a partir de medidas ultrassonográficas e morfométricas, e validação dos modelos de regressão - Conte, Bianchecci Danielli (2011)
This study aimed to predict the fillet weight (PF) and fillet yield (RF) of Nile tilapia (Oreochromis niloticus) from external measures, measured by morphometry and measures of epiaxial muscles using ultrasound and validate the estimated equations using another sample biometric data. A total of 102 adult fish GIFT lineage, reversed males weighing between 260 and 580 g had the total weight (PT) and body circumference average (CR) all measured by ultrasonography in four predefined body regions (1) between the basis of anterior (2) between the basis of anteriour insertion of anal fin to the last hard ray of dorsal fin. (3) between the final insertion of anal and dorsal fins and (4) between the ventral and dorsal insertion of caudal fin. The prediction equations from the measurements performed on 50 samples were analyzed by statistical procedures backward and stepwise. The measurements made in remaining 52 samples were used for validation of predictive equations to PF and RF. The validation were made from adjustment of linear models first degree of values observed above the values predict on each regression equation set. The equations PFx and RFx estimated from data collected of ultrasound images showed coefficient of determination (R2) of 0.53 (PF1 = -17.35 + 3.66HD2 45.20LE4 + 0.55AE2 + 4.64AE4) e 0.15 (RF1 = 26.66 + 0.043AE2), in backward, and 0.53 (PF2 = -58.03 + 5.65HE4 + 0.33AD1 + 0.65AD2) e 0.19 (RF2 = 25.02 + 0.051AD2), in stepwise. The inclusion of measures of CR and PT as regressive equations did allow the equations to show higher values of R2 such as 0.97 (PF3= - 52.25 1.26HE1 2.03HE3 + 0.40PT +0.51CR e PF4 = -18.12 1.20HE1 + 0.425PT) and 0.73 (RF3 = 17.83 0.29HE1 0.49HE3 + 0.02PT + 0.13CR), in backward and stepwise, and 0.68 (RF4 = 26,14 - 0,27HE1 + 0,027PT), in stepwise, and lower values of mean square of residue that these regression models presented high adherence to data of PF and RF. About the validation of prediction equations all of it were effective in estimating the PF and RF in the sample evaluated. The equations (P = 1.0000) PF3, PF4 (P = 0.5401), RF3 (P = 1.0000) and RF4 (P = 0.8363) were the most accurate and applicable in predicting PF and RF in Nile tilapia. The height of the left side body regions 1 and 3, measured by ultrasound images, together with the average body weight and circumference, are important in predicting of regressive of PF and RF of Nile tilapia. The regression equations, PF3, PF4, RF3, and RF4 are recommended for estimating the PF and RF of Tilapia in phenotypic males adult Nile tilapia GIFT lineage, weighing between 260 and 580 g